The epidemiological study of congenital anomalies and their possible risk factors in teaching hospital in MGM Kalamboli, Navi Mumbai - Kamble, Vidya; Patil, Shaifali; Bhatia, Tulsi; Thaware, Pradnya; Mathur, Pushpa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Congenital anomaly, a health problem in India, is a defective morphogenesis during early foetal life at cellular level. Purpose of our study was to determine the detection rate of congenital anomalies & their epidemiological predisposing risk factors with detailed history withdrawn among women visited in MGM Hospital, Kalamboli, Navi Mumbai, between May 2012 to May 2014. Methods: This is a Retrospective study. In this study period of 2 years, 69 pregnant women were diagnosed with congenital anomalies during their prenatal Ultrasonographic examinations. We studied these sonographic reports with the risk factors associated with occurrence of congenital anomalies. Results: Out of 2000 visited women, 69 were detected with congenital anomalies. Incidence rate was about 3.45%. Major &maximum anomalies were found in CNS & Renal system. CNS-32.88%, renal-40.58%, multiple system anomalies-5.79%. Risk factors mostly associated with these anomalies were age, race, residency, social status, H/O consanguineous marriage, H/O DM & GDM, literacy. Congenital anomalies were more seen in rural, low socioeconomic & illiterate population. Conclusions: Early diagnosis, prenatal evaluation, routine ANC care, better repo & good quality USG will be helpful for genetic counselling & clinical management.